Modeling the Re-appearance of a Crashed Airplane on Gauligletscher, Switzerland - Compagno, Loris; Jouvet, Guillaume; Bauder, Andreas; Funk, Martin; Church, Gregory; Leinss, Silvan; Lüthi, Martin P. (Frontiers in Earth Science, 2019)
In this study we used a modelling approach to reconstruct the space-time trajectory of the Dakota airplane which crashed on the Gauligletscher in 1946 and was subsequently buried by snow accumulation. Our aim was to localize its present position and predict when and where it would re-appear at the surface. For that purpose, in a first step we modelled the ice flow field and the evolution of Gauligletscher from 1946 using a combined Stokes ice flow and surface mass balance model, which was calibrated with surface elevation and velocity observations. In a second step the modelled ice velocity fields were integrated forward-in-time, starting from the crash location. We found that the main body of the damaged Dakota aircraft might not emerge, as anticipated; in the vicinity of the pieces released at the surface between 2012 and 2018, but about 1 km upstream, between 2027 and 2035. Our modelling results indicate that the recently found pieces of the Dakota might have been removed from the original aircraft location and moved down-glacier before being abandoned in the late 40s.